Description of a new species of the genus Ruspolia (Schulthess, 1898) (Conocephalinae: Copiphorini) from Kashmir, India - Shah, Muzamil Syed; Usmani, Mohd. Kamil; Ali, Mohd; Dar, Afaq Ahmad (Zootaxa, 2021)
Karny (1912) proposed the tribe Copiphorini within the subfamily Conocephalinae, family Tettigoniidae. Copiphorini is one of the four tribes of Conocephalinae. The members of this tribe are characterized by slanting head shape and notched frons. The specimens for this study were collected in different regions of the Kashmir valley in the year 2020. A brief morphological description of the genus and new species is given. Also, a key to Indian species is provided. The type specimen has been deposited in the Museum of Zoology Department AMU.